Antimicrobial resistance in indicator Escherichia coli from small-scale swine herds in north-eastern Thailand - Karlsson, David (2016)
Antimicrobial resistance (AMR) is a fast growing problem throughout the world, and as a consequence effective treatment of various infections is jeopardized. This results in prolonged illness and increased mortality amongst patients as well as increased health care costs. It is known that excessive usage of antimicrobial drugs contributes to the development of antimicrobial resistance. There have also been reports of resistant bacteria spreading from animals to human. However, the full magnitude of the problem worldwide is still not known. In a joint effort to combat AMR, the Food and Agricultural Organization of the United Nations (FAO), the World Health Organization (WHO) and the World Organization for Animal Health (OIE) therefore encourages countries to develop harmonized AMR-monitoring programs to map the AMR in food animals. The pig industry in Southeast Asia has been steadily growing the last decades; however the knowledge about the occurrence of AMR is poor. In Thailand there have been studies that map AMR in pigs; however there is a lack of standardization and harmonization, which makes national data difficult to interpret. The purpose of this study was to investigate the occurrence of antimicrobial resistance in small-scale swine herds in Khon Kaen Province in the northeast of Thailand, using intestinal Escherichia coli as indicator bacteria. Furthermore the purpose was also to compare the result from this study with data from similar studies from Thailand and other countries. Twenty-five farms were visited, which housed a maximum of twenty sows each. To help gain insight in pig farming in Thailand and help identify possible factors affecting AMR, the person responsible for the pigs at each farm was asked to fill in a questionnaire with questions about the farm, husbandry, antibiotic usage, vaccination regimes etc. On each farm three samples were collected in the form of rectal swabs from three different healthy sows. A total of 69 samples were collected. From each sample E. coli was cultured and tested for antimicrobial susceptibility using a standardized broth microdilution method to determine minimum inhibitory concentrations (MICs). Resistant isolates of E. coli was found on all farms. Resistance against tetracycline (75.3% of the isolates), ampicillin (69.6%) and sulfamethoxazole (60.8%) were the most common. Multiresistance could be seen in 69.5% of the isolates. One suspected extended spectrum beta-lactamase producing (ESBL)-isolate was found. Statistical analyses to identify risk factors for AMR were difficult to perform due to the small number of observations and those made must therefore be considered to lack in statistical power. When compared to OECD countries the level of AMR was generally higher in this study. When compared to studies from Thailand made on larger farms, the AMR levels were generally lower in this study. Antimicrobial resistance seems to be common in small-scale swineherds in north-eastern Thailand. However, a national standardized and harmonized monitoring program is needed to fully evaluate the situation.